MODIFICATION OF MYOCARDIUM FUNCTION AND PERFUSION AFTER LIVER TRANSPLANTATION. RESULTS OF MYOCARDIAL SCINTIGRAPHY - Y.O. Malinovskaya; E.N. Ostroumov; E.D. Kotina; Y.G. Moysyuk (Вестник трансплантологии и искусственных органов)
Aim evaluated function and perfusion of myocardium in 12 cirrhotic patients before and after liver transplantation (LT).Materials and methods. ECG-gated single photon emission computed tomography (SPECT) was used.Results. It was found that hyperdynamics diminished liver transplantation: left ventricle (LV) end-systolic volume (ESV) rose from 23 to 33 ml (p = 0,026), LV ejection fraction decreased staying normal from 76 до 60% (p = 0,08), calculated cardiac output declined from 4941 to 3066 ml/min (p = 0,009), peak ejection rate (PER) from 314 to 218 ml/sec, (p = 0,003), peak fi lling rate decreased from 248 to 182 ml/sec (p = 0,037), eccentricity coeffi cient also decreased from 0,81 to 0,77 (p = 0,028). Local alteration of perfusion was found only in 2 cases.Conclusion. Hyperdynamic systolic dysfunction and diastolic dysfunction improve after liver transplantation. Further studies are required to estimate the applicability of SPECT in liver transplantation candidates’ evaluation.